Student Facilitator and Explaining Assisted by Pop-Up Books: Effects on Fifth-Grade Elementary School Students’ Mathematics Learning Outcomes - Anggita Lubis, Fani; Siregar, Nurdiana; Nur Kamalia Siregar, Lailatun (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Elementary mathematics learning requires instructional strategies that allow students to understand concepts, explain ideas, and participate actively. This study aimed to analyze the effect of the Student Facilitator and Explaining (SFAE) model assisted by pop-up books on the mathematics learning outcomes of fifth-grade students at SD Al-Ittihadiyah Mamiyai. A quantitative quasi-experimental non-equivalent pretest-posttest control group design was employed. The population consisted of 142 students, while the sample comprised 38 fifth-grade students selected through purposive sampling and assigned to experimental and control groups. Learning outcomes were measured using a 15-item multiple-choice test with a Cronbach’s Alpha reliability coefficient of 0.841. Data were analyzed using descriptive statistics, normality and homogeneity tests, and an independent-samples t-test. The pretest means of the experimental and control groups were 65.48 and 61.82, respectively. After instruction, the experimental group obtained a posttest mean of 76.86 (SD = 9.372), compared with 67.82 (SD = 9.926) in the control group. The homogeneity test yielded p = .878, and the data met normality assumptions. The posttest comparison produced p = .007, indicating a significant difference at the .05 level. These findings suggest that SFAE assisted by pop-up books can support mathematics learning outcomes by engaging students in explaining and communicating mathematical concepts.